User Involvement, Training and Education, and Top Management Support for Accounting Information System Performance: Keterlibatan Pemakai, Pelatihan Dan Pendidikan, Serta Dukungan Manajemen Puncak Terhadap Kinerja Sistem Informasi Akuntansi - Sri Wahjuni Latifah; Wibi Abitama (Journal of Accounting Science, 2021)
The purpose of this research is to find out the influence of user involvement, training and education, and top management support on the performance of accounting information systems. The dependent variable in this study is the performance of accounting information systems. While the independent variables are user involvement, training and education, and top management support. The sample taken in this study were 54 respondents who were employees of the Sentani Malang Oncology Hospital who used the accounting information system. The analysis technique used descriptive statistical analysis and PLS analysis using warpls7. The results of this study show: (1) There is a positive and significant direct influence between user involvement on the performance of the accounting information system, (2) There is a positive and significant direct influence between training and education on the performance of the accounting information system, (3) There is a positive and significant direct influence between top management support on the performance of the accounting information system.